The Urgency of Notary Deed in Supporting Sustainable Economic Growth in Riau - Abdillah, Satrio; Sundari, Eva (JURNAL AKTA, 2024)
This research aims to investigate and analyze the creation of a conducive business climate using notary deed in Riau. The results show that notary deed play a central role in creating a stable and attractive business environment for sustainable economic growth through interviews and documentation, including maximizing Nvivo 12 Plus analysis for data coding. In this context, business transactions become legally valid with notary deed to increase confidence in investing and conducting business. Even though the concept is essential in increasing legal certainty and creating a conducive business climate, several challenges are faced in the implementation, including awareness and education, cost and time, bureaucratic processes, and changing regulations.